Three recommendations for advancing adaptation tracking emerge from a review of 53 African - Nowak, Andreea C.; Njunguna, Lucy (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Three recommendations 1. Amplify and scale out recent progress on adaptation tracking through targeted capacity building, enhanced investments in M&E systems, and south-south knowledge exchange. 2. Classify indicators to support a common framing and aggregation for adaptation tracking. 3. Expand the scope of adaptation tracking indicators to pair the current activity-focused approach with outcome indicators to document impact.